2021
DOI: 10.3390/jof7110927
|View full text |Cite
|
Sign up to set email alerts
|

Fungi Associated with Postharvest Diseases of Sweet Potato Storage Roots and In Vitro Antagonistic Assay of Trichoderma harzianum against the Diseases

Abstract: Sweet potato is the 11th most important food crop in the world and an excellent source of nutrition. Postharvest diseases were monitored in sweet potato storage roots collected from the local markets in Korea during 2021. Several diseases including Fusarium surface and root rot, charcoal rot, dry rot, and soft rot were observed in the postharvest sweet potatoes. A total of 68 fungal isolates were obtained from the diseased samples, and the isolates were grouped into 8 different fungal colony types. Based on mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 42 publications
3
10
0
Order By: Relevance
“…Martínez-Salgado et al (2021) reported the highest percentage of growth inhibition of this phytopathogen (71.11%) by T. koningipsis. According to studies by Paul et al (2021), the antagonism exhibited by T. harzianum ranged between 75.01 and 78.22%. A slightly higher inhibition rate (72.42%) than in the present study was observed by El-Benawy et al, (2020) by the T. atroviride isolate T22.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Martínez-Salgado et al (2021) reported the highest percentage of growth inhibition of this phytopathogen (71.11%) by T. koningipsis. According to studies by Paul et al (2021), the antagonism exhibited by T. harzianum ranged between 75.01 and 78.22%. A slightly higher inhibition rate (72.42%) than in the present study was observed by El-Benawy et al, (2020) by the T. atroviride isolate T22.…”
Section: Discussionmentioning
confidence: 99%
“…Screening of the antagonist potential of Trichoderma isolates has been demonstrated in scientific works for several plant pathogenic fungi, such as Macrophomina phaseolina (El-Benawy et al, 2020, Choudhary et al, 2021, Martínez-Salgado et al, 2021, Paul et al, 2021; Fusarium spp. (Pellan et al, 2020;Kumar et al, 2021;Yassin et al, 2021); Sclerotium rolfsii (Kotasthane et al, 2014;Kamel et al, 2020;Blanco et al, 2021) and Sclerotinia sclerotiorum (Marques et al, 2016;Amaral et al, 2018;Sumida et al, 2018;Carvalho et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In dual confrontation assays, two strains of T. harzianum , CMML20-26 and CMML20-27, showed strong antagonistic activity against several sweet potato postharvest pathogens, including Fusarium ipomeae, F. oxysporum, F. solani , Penicillium citrinum¸ P. rotoruae, Aspergillus wentii, Mucor variicolumellatus and M. phaseolina [ 108 ]. T. harzianum MRI001 can mycoparasite F. oxysporum , A. alternata, Aspergillus carbonarius, and A. flavus , overgrowing the pathogens and reducing the production of the mycotoxins ochratoxin and aflatoxin B 1 , produced by A. carbonarius and A. flavus respectively [ 109 ].…”
Section: Biocontrol Potential Of Registered Trichoderma ...mentioning
confidence: 99%
“…1 The organisms are distributed in the air, soil and in storage to constitute storage fungi. [2][3][4] A wide range of fungal species which cause different types of decay in sweet potato root tubers originate from different sources. 5,6 Food security and sustainability is one of the ways of addressing food scarcity and shortage due to the activities of fungi.…”
Section: Introductionmentioning
confidence: 99%